Body weight status and dietary intake of Malaysian children with autism spectrum disorder - Eow, Shiang Yen; Gan, Wan Ying; Awang, Hamidin (Elsevier, 2021)
Children with Autism Spectrum Disorder (ASD) in general, possess selective eating habits and sensory sensitivity that predispose them to the risk of poor nutritional status. Nutritional status of children is important for optimal physical and cognitive development and reduction of the risk of chronic diseases in the future. Given the limited information on the body weight status and nutrient intake of Malaysian children with ASD, this study, therefore, assessed the body weight status and dietary intake of children with ASD in an autism intervention centre in Kuala Lumpur. A total of 224 children with ASD aged 3–7 years (82.6% boys and 17.4% girls) and their mothers participated in this study. Mothers completed a self-administered questionnaire on the socio demographic background and recorded a 3-day food diary of their children with ASD at home. The researcher measured body weight and height of the children with ASD in the centre. The prevalence rates of underweight, stunting, wasting/thinness, and overweight/obesity were 9.3%, 8.0%, 4.0%, and 21.5%, respectively. Total energy and protein intakes were adequate for most of the children with ASD but calorie from fat was higher than the recommendation. A majority of the children with ASD in this study did not meet the RNI requirements for fibre (99.6%), thiamine (67.4%), vitamin C (50.9%), vitamin D (98.2%), vitamin E (74.6%), vitamin B12 (64.3%), folate (88.8%), calcium (90.2%) and zinc (77.2%). More girls showed inadequate intakes of vitamin C, niacin and vitamin B12 than boys. Children with ASD in this study showed poor body weight status and inadequate intake of several essential nutrients. Nutritional intervention programmes in improving nutrient adequacy and regular anthropometric measurements are recommended to be carried out in order to improve nutritional status of children with ASD.